American born Chinese - Yang, Gene Luen; Pien, Lark (First Second, 2006)
Jin Wang starts at a new school where he's the only Chinese-American student. When a boy from Taiwan joins his class, Jin doesn't want to be associated with an FOB like him. Jin just wants to be an all-American boy, because he's in love with an all-American girl. Danny is an all-American boy: great at basketball, popular with the girls. But his obnoxious Chinese cousin Chin-Kee's annual visit is such a disaster that it ruins Danny's reputation at school, leaving him with no choice but to transfer somewhere he can start all over again. The Monkey King has lived for thousands of years and mastered the arts of kung fu and the heavenly disciplines. He's ready to join the ranks of the immortal gods in heaven. But there's no place in heaven for a monkey. Each of these characters cannot help himself alone, but how can they possibly help each other? They're going to have to find a way - if they want fix the disasters their lives have become--Publisher's description.
Michael L. Printz Award for Excellence in Young Adult Literature, 2007
Story 1: "All Jin Wing wants is to fit in. When his family moves to a new neighborhood, he suddenly finds that he's the only Chinese American student at the school. Jocki and his bullies pick on him constantly, and he has hardly any friends. Then, to make matters worse, he falls in love with an all-American girl." Story 2: "Born to rule over all the monkeys in the world, the story of the Monkey King is one of the oldest and greatest Chinese fables. Adored by his subjects, master of the arts of kung-fu, he is the most powerful monkey on Earth. But the Monkey King doesn't want to be a monkey. He wants to be hailed as a god ..." Story 3: "Chin-Kee is the ultimate negative Chinese stereotype, and he's ruining his cousin Danny's life. Danny's a basketball player, a popular kid at school, but every year Chin-Kee comes to visit, and every year Danny has to transfer to a new school to escape the shame. This year, though, things quickly go from bad to worse" -- Publisher's description.
Jin Wang starts at a new school where he's the only Chinese-American student. When a boy from Taiwan joins his class, Jin doesn't want to be associated with an FOB like him. Jin just wants to be an all-American boy, because he's in love with an all-American girl. Danny is an all-American boy: great at basketball, popular with the girls. But his obnoxious Chinese cousin Chin-Kee's annual visit is such a disaster that it ruins Danny's reputation at school, leaving him with no choice but to transfer somewhere he can start all over again. The Monkey King has lived for thousands of years and mastered the arts of kung fu and the heavenly disciplines. He's ready to join the ranks of the immortal gods in heaven. But there's no place in heaven for a monkey. Each of these characters cannot help himself alone, but how can they possibly help each other? They're going to have to find a way - if they want fix the disasters their lives have become--Publisher's description.
Story 1: "All Jin Wing wants is to fit in. When his family moves to a new neighborhood, he suddenly finds that he's the only Chinese American student at the school. Jocks and bullies pick on him constantly, and he has hardly any friends. Then, to make matters worse, he falls in love with an all-American girl." Story 2: "Born to rule over all the monkeys in the world, the story of the Monkey King is one of the oldest and greatest Chinese fables. Adored by his subjects, master of the arts of kung-fu, he is the most powerful monkey on Earth. But the Monkey King doesn't want to be a monkey. He wants to be hailed as a god ..." Story 3: "Chin-Kee is the ultimate negative Chinese stereotype, and he's ruining his cousin Danny's life. Danny's a basketball player, a popular kid at school, but every year Chin-Kee comes to visit, and every year Danny has to transfer to a new school to escape the shame. This year, though, things quickly go from bad to worse"--Publisher's description.
"Alternates three interrelated stories about the problems of young Chinese Americans trying to participate in the popular culture. Presented in comic book format"--Title page verso.
Keywords: Comic books, strips, etc. / sears; School stories. / sears; Identity (Psychology) / Fiction. / sears; Chinese Americans / Fiction. / sears; Enfants d'immigrés / Bandes dessinées. / ram; Enfants appartenant à des minorités / Bandes dessinées. / ram; Michael L. Printz Award / fast; Schools / fast; Identity (Psychology) / fast; Graphic novels / fast; Chinese Americans / fast; YOUNG ADULT FICTION / People & Places / United States / Asian American. / bisacsh; YOUNG ADULT FICTION / Comics & Graphic Novels. / bisacsh; Racisme / États-Unis / Romans, nouvelles, etc. pour la jeunesse.; Adolescents / Romans, nouvelles, etc. pour la jeunesse.; Écoles / Romans, nouvelles, etc. pour la jeunesse.; Écoles / Bandes dessinées.; Identité (Psychologie) / Romans, nouvelles, etc. pour la jeunesse.; Identité (Psychologie) / Bandes dessinées.; Américains d'origine chinoise / Romans, nouvelles, etc. pour la jeunesse.; Américains d'origine chinoise / Bandes dessinées.; Cartoons and comics.; Schools / Fiction; Identity / Fiction.; Chinese Americans / Fiction.; Racism / United States / Juvenile fiction.; Racism / United States / Comic books, strips, etc.; Interpersonal relations / Juvenile fiction; Interpersonal relations / Comic books, strips, etc.; Teenagers / Juvenile fiction; Teenagers / Comic books, strips, etc.; Schools / Juvenile fiction; Schools / Comic books, strips, etc.; Identity (Psychology) / Juvenile fiction; Identity (Psychology) / Comic books, strips, etc.; Chinese Americans / Juvenile fiction; Chinese Americans / Comic books, strips, etc.; Bandes dessinées sur l'école. / rvmgf; Dessins humoristiques. / rvmgf; School comics / lcgft; Fantasy comics / lcgft; Graphic novels / lcgft; Young adult fiction. / gsafd; Juvenile works / fast; Fiction / fast; Comics (Graphic works) / fast; cartoons (humorous images) / aat; Cartoon; Michael L. Printz Award winner, / 2007; Young adult fiction.; Young Adult Fiction.